2010
DOI: 10.1097/ico.0b013e3181d9284b
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Corneal Biomechanical Parameters After Phacoemulsification With Intraocular Lens Implantation

Abstract: Both CH and CRF decreased briefly at 1 day after cataract surgery but soon recovered to the preoperative levels, suggesting that cataract surgery does not induce a significant change in corneal biomechanics, except for 1 day postoperatively. The corneal thickness may play some role in corneal biomechanics even in postcataract eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
4
14
0
1
Order By: Relevance
“…They stated that these values were approaching preoperative values in postoperative 1st and 3rd months. Consequently they concluded that cataract surgery did not have a statistically significant effect on corneal biomechanical values except postoperative first day (14). Similarly in our study, there was a statistically significant decrease in CH and CRF values on postoperative day 1, and this decrease was also observed at postoperative 1st week and 1st month.…”
Section: Discussionsupporting
confidence: 79%
“…They stated that these values were approaching preoperative values in postoperative 1st and 3rd months. Consequently they concluded that cataract surgery did not have a statistically significant effect on corneal biomechanical values except postoperative first day (14). Similarly in our study, there was a statistically significant decrease in CH and CRF values on postoperative day 1, and this decrease was also observed at postoperative 1st week and 1st month.…”
Section: Discussionsupporting
confidence: 79%
“…Prior studies have demonstrated that there are no detectable changes in corneal biomechanical parameters as a result of intraocular surgery, including phacoemulsification, beyond the 3-month postoperative period. [30][31][32][33] All outputs were reviewed to ensure that films were not interrupted by eyelid movements, and readings were not disrupted by eyelash impact on the corneal surface. Corvis measurements were obtained in duplicates and results were averaged, to minimize effects of test-retest variability noted in prior studies.…”
Section: Subjectsmentioning
confidence: 99%
“…In a study by Falkenberg et al, 18 there was a mean increase in CCT of 37 mm 1 day after cataract surgery. In another study, 19 we also found that CH and CRF decreased briefly 1 day after cataract surgery without LRIs but soon recovered to the preoperative levels.…”
Section: Discussionmentioning
confidence: 64%
“…Multiple comparisons showed a significant difference between preoperative and 1-day postoperative measurements (PZ.004) but not between preoperative measurements and postoperative measurements at 1 week (PZ.19), 1 month (PZ.20), or 3 months (PZ. 19).…”
Section: Resultsmentioning
confidence: 95%